Morpho-agronomic Characterization of Cucumber (Cucumis sativus) Germplasm for Yield and Yield-associated Traits - Mainali, Ram P; Jyakhwa, Sunmoon (International Journal of Applied Sciences and Biotechnology, 2023)
Nepal possesses a rich diversity of cucumber landraces and their wild relatives. The first step towards harnessing the potential of these landraces in crop improvement programs is to identify the amount of genetic variation present among them. This research aimed to evaluate 18 cucumber accessions collected from different regions of Nepal and assess their agro-morphological variation in terms of yield and yield-associated traits under polyhouse condition. A research trial was conducted using Randomized Complete Block Design with two replicates at the National Agriculture Genetic Resources Centre (NAGRC), Khumaltar in 2019. The accessions were characterized using various qualitative and quantitative descriptors, with six focusing on traits related to the fruits of the plant and three on phenology and morphology. The results revealed significant variations among the genotypes for all studied traits. Bhaktapur Local was an excellent genotype for recording yield and associated traits, like fruit dimension, number of fruits per plant and yield per plant, making it the most promising genotype, however, Genebank accessions, such as NGRC08671, NGRC07716 and NGRC08668 could be excellent choices for yield associated traits. Correlation analysis indicated a positive relationship between yield and fruit length, fruit width, and total number of fruits per plant, while vine length was positively correlated with the total number of fruits produced per plant. This study identified several genotypes with desirable traits for yield and yield-associated characteristics, which could be valuable in the development of high-yielding cucumber varieties with superior morphological and agronomic traits in the future. Int. J. Appl. Sci. Biotechnol. Vol 11(1): 30-36.